Localization and expression of CaBP1/caldendrin in the mouse brain - Kim, Kristin Y. (2014)
Ca(2+) binding protein 1 (CaBP1) and caldendrin are alternatively spliced variants of a subfamily of Ca(2+) binding proteins with high homology to calmodulin. Although CaBP1 and caldendrin regulate effectors including plasma membrane and intracellular Ca(2+) channels in heterologous expression systems, little is known about their functions in vivo. Therefore, we generated mice deficient in CaBP1/ caldendrin expression (C-KO) and analyzed the expression and cellular localization of CaBP1 and caldendrin in the mouse brain. Immunoperoxidase labeling with antibodies recognizing both CaBP1 and caldendrin was absent in the brain of C-KO mice, but was intense in multiple brain regions of wild-type mice. By western blot, the antibodies detected two proteins that were absent in the C-KO mouse and consistent in size with caldendrin variants originating from alternative translation initiation sites. By quantitative PCR, caldendrin transcript levels were far greater than those for CaBP1 particularly in the cerebral cortex and hippocampus. In the frontal cortex but not in the hippocampus, caldendrin expression increased steadily from birth. By double-label immunofluorescence, CaBP1/caldendrin was localized in principal neurons and parvalbumin-positive interneurons. In the cerebellum, CaBP1/caldendrin antibodies labeled interneurons in the molecular layer and in basket cell terminals surrounding the soma and axon initial segment of Purkinje neurons, but immunolabeling was absent in Purkinje neurons. We conclude that CaBP1/ caldendrin is localized both pre- and postsynaptically where it may regulate Ca(2+) signaling and excitability in select groups of excitatory and inhibitory neurons.